Brushes with the Law: A Conservation Scientist's Perspective on Legal Solutions and Impediments from Scottish Wildcats to African Lions*. Issue 1 (2nd January 2019) - Macdonald, D.W.
Abstract: I suggest here that the requirements for conservation evidence within regulation are cyclical in nature, and I describe the key stages in this cycle of conservation regulation. In particular, I focus on: (1) the type of evidence required (illustrated by the case of water voles disrupted by riverside development), (2) the clarity of evidence in terms of its implications for policy (illustrated by the harrowing case of the endangered Scottish wildcat hybridising with the pestilential feral domestic cat), (3) the actual impact such evidence has in practice (illustrated by the legal confusions arising from the changing taxonomy of protected species), and (4) the role of evidence in assessing regulatory efficacy (which returns us to point 1 in the cycle) (illustrated by evidence of the (in)humaneness of, for example, rodent traps, various instances of wildlife trade, and the efficacy of international conventions). The article concludes with a series of reflections on how conservation researchers might engage with legal experts and practitioners for the benefit of wildlife conservation in the twenty-first century: through transdisciplinary research, ethically informed and actively applied.